Performance of dispatcher-assisted cardiopulmonary resuscitation integrating with mouth-and-nose covering instructions during the COVID-19 pandemic: a population-based retrospective study - Hideki Asai; Hidetada Fukushima; Yasuyuki Kawai; Keita Miyazaki; Kouji Yamamoto; Arisa Kinoshita; Hirozumi Okuda (BMC Emergency Medicine)
Abstract Background The coronavirus disease 2019 (COVID-19) pandemic, which emerged in late 2019, compelled people to change their behavior globally. Due to concerns about potential aerosol transmission during chest compressions, a modified dispatcher-assisted cardiopulmonary resuscitation (DACPR) protocol incorporating mouth-and-nose covering instructions was introduced in Nara, Japan. This study examined its impact on DACPR performance during the COVID-19 pandemic. Methods This is a retrospective before-after study. DACPR performance data from the Nara Wide Area Fire Department were analyzed, comparing the non-pandemic period (March 2019 to February 2020) with the pandemic period (November 2020 to October 2021). The primary outcome was the time from emergency call acceptance to the first chest compression (T3). Secondary outcomes included the time to cardiac arrest recognition (T1), the time to start of DACPR instructions (T2), DACPR implementation rate, and adherence to infection prevention instructions. Results The implementation of the modified protocol did not significantly alter the overall DACPR rate (406, 50.3% in the non-pandemic vs. 390, 47.2% in the pandemic; p =.214). Although the difference was relatively small, a statistically significant prolongation of T3 was observed during the pandemic period (246.0 s vs. 261.5 s, p <.05). Compliance with mouth-and-nose covering instructions among dispatchers was relatively low (43.1%). Among cases where such instructions were provided, only 21.4% of bystanders fully adhered to the protocol (both the bystander and the patient covering their mouth and nose). However, dispatcher-provided instructions significantly increased the likelihood of bystanders wearing masks and covering the patient’s mouth and nose. Multivariable analysis did not identify the protocol implementation as a significant factor influencing T3. Conclusions This study demonstrated that the modified DACPR protocol incorporating infection prevention measures was associated with a statistically significant delay of approximately 15.0 s in CPR initiation. However, given the low adherence rate, the overall impact of these measures on DACPR performance was limited. These findings highlight the need to increase adherence to infection prevention measures while minimizing delays in life-saving interventions, particularly during pandemics caused by airborne pathogens.